2008
DOI: 10.1086/591972
|View full text |Cite
|
Sign up to set email alerts
|

New Treatment Approach in Indian Visceral Leishmaniasis: Single‐Dose Liposomal Amphotericin B Followed by Short‐Course Oral Miltefosine

Abstract: ClinicalTrials.gov identifier: NCT00370825 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
96
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(99 citation statements)
references
References 18 publications
0
96
0
3
Order By: Relevance
“…Benaim et al (47) demonstrated the specific antiparasitic effects of amiodarone and the synergistic effects of combinations with posaconazole against Trypanosoma cruzi, in vitro and in vivo; similar effects were more recently reported for Leishmania mexicana and miltefosine (48). There is a growing recognition of the relevance of combination therapies to address several limitations of currently available antiLeishmania drugs, including toxicity as well as natural and acquired drug resistance (1,3,(49)(50)(51)(52). Indeed, several studies have reported the superior efficacies of combination therapies against leishmaniasis, and some of them demonstrated the synergic effects of combinations of amphotericin B with other available drugs, such as miltefosine, paromomycin, meglumine antimoniate, or azythromycin (49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 74%
“…Benaim et al (47) demonstrated the specific antiparasitic effects of amiodarone and the synergistic effects of combinations with posaconazole against Trypanosoma cruzi, in vitro and in vivo; similar effects were more recently reported for Leishmania mexicana and miltefosine (48). There is a growing recognition of the relevance of combination therapies to address several limitations of currently available antiLeishmania drugs, including toxicity as well as natural and acquired drug resistance (1,3,(49)(50)(51)(52). Indeed, several studies have reported the superior efficacies of combination therapies against leishmaniasis, and some of them demonstrated the synergic effects of combinations of amphotericin B with other available drugs, such as miltefosine, paromomycin, meglumine antimoniate, or azythromycin (49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 74%
“…Amphotericin B, particularly in liposomal formulation (68), has become the drug of choice in developed countries and where antimony resistance is problematic, but issues of cost and toxicity remain (69). Oral miltefosine, recently shown to be effective in VL (70), has also more recently been shown to be compatible for use in combination therapy with Amphotericin B (71). Of note, it has been long recognized from studies in experimental VL that the efficacy of the antimonial drugs is exquisitely dependent upon host immune function, being modulated by a number of key T cell-derived cytokines (11,14,44).…”
Section: Discussionmentioning
confidence: 99%
“…Strict control of drug delivery and prevention of drug resistance would also be facilitated by the use of short combined treatments such as those currently being studied in India. 29 Increased risk of treatment failure in patients coming from Nepalese districts close to the areas of Bihar where 4,6,12 The intense cross-border migration of populations between Nepal and Bihar, considered an important risk factor for the spread of VL in this region, 27 would also suggest a spread of resistant strains of L. donovani from Bihar to Nepal. 30 …”
Section: Discussionmentioning
confidence: 99%